Seeking harmony: estimands and sensitivity analyses for confirmatory clinical trials. (August 2016) - Mehrotra, Devan V; Hemmings, Robert J; Russek-Cohen, Estelle; ,
In October 2014, the Steering Committee of the International Conference on Harmonization endorsed the formation of an expert working group to develop an addendum to the International Conference on Harmonization E9 guideline ("Statistical Principles for Clinical Trials"). The addendum will focus on two topics involving randomized confirmatory clinical trials: estimands and sensitivity analyses. Both topics are motivated, in part, by the need to improve the precision with which scientific questions of interest are formulated and addressed by clinical trialists and regulators, specifically in the context of post-randomization events such as use of rescue medication or missing data resulting from dropouts. Given the importance of these topics for the statistical and medical community, we articulate the reasons for the planned addendum. The resulting "ICH E9/R1" guideline will include a framework for improved trial planning, conduct, analysis, and interpretation; a draft is expected to be ready for public comment in the second half of 2016.